PERANAN PSIKOLOGI SOSIAL DALAM PEMBERDAYAAN MASYARAKAT YANG BERKELANJUTAN - Artika Cesar Aura Devi, Chyntia Martini, Nadia Karin, Zahra Permata Sari, Sulistiasih (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Community empowerment is a process of providing power in the form of opportunities, knowledge, skills and materials, thereby making the powerless become powerful or helping to increase the ability, capacity and self-confidence of the community so that they have the power/strength to overcome the problems they face in order to achieve a better life, so that they can determine a future that suits their wishes. This is where the role of the government, through government efforts, assistance and intervention, is hoped that the community will become more empowered, which in turn will make the people more prosperous in life. The phenomenon of social psychology in empowerment and community development which refers to how individuals and groups interact in a social context, and how these interactions influence behavior, identity and community welfare. In the context of community empowerment and development, social psychology plays an important role in understanding and overcoming various social and economic challenges. Social psychology also helps in understanding how socialization, social norms, and social identity influence individual and group behavior. In addition, it can be used to develop effective strategies to improve the social and economic welfare of society.